The last link of the x-aminobutyric acid series: the five conformers of β-aminobutyric acid. Issue 22 (29th May 2018) - León, I.; Peña, I.; Cabezas, C.; Alonso, E. R.; Alonso, J. L.
Abstract : Structural characterization of β-aminobutyric acid by rotational spectroscopy. Abstract : β-Aminobutyric acid is a non-proteinogenic amino acid that is known to protect plants against various pathogens. Its structure is midway between α-aminobutyric acid and γ-aminobutyric acid. The structural differences in the position of the amino group in the conformational stabilization of β-aminobutyric acid have been studied by laser ablation Fourier transform microwave spectroscopy. Five conformers have been detected, and their rotational and quadrupole coupling constants of the 14 N nucleus determined. Three of the conformers, including the most stable structure, are stabilized by a non-bifurcated N–H⋯OC intramolecular hydrogen bond. The other two conformers possess a N⋯H–O intramolecular interaction. In this work we highlight that β-aminobutyric acid shows the conformational peculiarities of α-aminobutyric acid and γ-aminobutyric acid completing the rotational spectroscopic study of the x -aminobutyric acid series.